Optimizing Steam to Electricity Ratio in Crude Palm Oil Refinery Captive Power Plant: A Six Sigma-DMAIC Capability Assessment - Anggriawan, Akbar; Susilawati, Anita; Mainil, Rahmat Iman (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This study applies the Six Sigma-DMAIC (Define, Measure, Analyze, Improve, Control) methodology combined with process capability analysis to enhance energy efficiency, specifically by reducing the steam to electricity ratio of a steam turbine. Initial measurements indicated a steam-to-electricity ratio of 4.5 to 5.34 kg/kWh, highlighting high steam consumption and poor efficiency. The process was unstable, with Cp and Cpk values of 0.30 and -0.16, and a defect rate exceeding 560,000 DPMO. Using an Ishikawa diagram, a vacuum leak in the steam turbine condenser was identified as the main cause of excessive steam consumption. After repairing the condenser, monitoring showed significant improvements, with the steam to electricity ratio reducing to 3.0 – 4.0 kg/kWh. Process capability improved, with Cp increasing to 1.39, Cpk to 1.02, and Z-bench to 3.05 (equivalent to 1,143 DPMO). The Anderson-Darling test confirmed a normal distribution (p-value = 0.464). Six Sigma-DMAIC effectively optimized steam turbine performance.